RE-OS SYSTEMATICS IN CHONDRITES AND THE FRACTIONATION OF THE PLATINUM GROUP ELEMENTS IN THE EARLY SOLAR SYSTEM - IMPLICATIONS FOR PARTIAL MELTING - Chen J.H.; Papanastassiou D.A.; Wasserburg G.J. (My University, 1998)
We have investigated the Re-Os system for samples of whole rock, metal, and sulfide from ordinary chondrites. Using closed-system analytical techniques, we found complete exchange between sample and tracer isotopes for silicate-containing samples and obtained precise and reliable Re-Os concentration measurements. Results on two Group IVA iron meteorites and on a silicate-rich iron (Steinbach, IVA-AN) are consistent with the IVA-IVB isochron and support the previous observation that IVA-IVB irons may be slightly older than IIAB irons. Data on whole-rock fragments and metal-rich separates from the St. Severin chondrite (LL6) show a large range in 187Re/188Os and in 187Os/188Os, which makes possible, in principle, the determination of a Re-Os internal isochron on a chondrite, for the first time. This Re-Os fractionation may be due to partial melting of FeNiS and macroscopic redistribution of metal and sulfide. The St. Severin data show a good correlation line on a 187Re-187Os evolution diagram. If this is considered to represent an internal isochron, it gives an age T = 4.68 +/- 0.15 AE [λ(187Re) = 1.64 x 10-11 a-1] and an initial (187Os/188Os)0 = 0.0953 +/- 0.0013. This age is in agreement with but slightly older than the more precise 187Re-187Os age for the IIAB irons as well as for irons from other groups (T = 4.61 +/- 0.01 AE). A St. Severin sulfide nodule has very low Re and Os concentrations and shows a young Re-Os model age (2.3 AE), indicating recent element remobilization. Whole rock and metal-rich separates of H-Group chondrites (H3 to H6) yield restricted ranges in 187Re/188Os (0.42-0.47) and 187Os/188Os (0.128-0.133). There is a systematic difference between Re/Os in the metal extracted from a chondrite and the bulk chondrite. This shows that there is a small but significant Re-Os fractionation within subsystems contained in the chondrites. From whole rock samples of H Group chondrites we calculate a mean 187Re/188Os = 0.423 +/- 0.007 and 187Os/188Os = 0.12863 +/- 0.00046, which may characterize the evolution of an average chondritic reservoir for Re-Os. The ordinary chondrite data plot close to the IIAB isochron, although the deviations found are larger than found for the irons. The Re-Os chronometer in iron meteorites is apparently controlled by the Re-Os fractionation due to fractional crystallization of liquid metal. Re-Os ages of iron meteorites give the time of crystallization of metal segregations and cores of early planetary bodies. In contrast, the behavior in ordinary chondrites, while also dominated by the metal phases, must reflect fractionation and transport on a local macroscopic scale within the chondrites between the metal phases after aggregation, due to partial melting of FeNiS or represent variable Re-Os fractionation of the metal phases prior to the accretion of the chondrites. However, for St. Severin, we attribute the major Re-Os fractionation to early heating of the meteorite, above the Fe-FeS eutectic. We do not consider that the Re-Os fractionation observed in other chondrites is due to the redistribution of Re and Os during chondrite metamorphism (including shock) but it may plausibly represent earlier stages of Re-Os fractionation for the different FeNi metal constituents prior to accretion.